Diagnostics of low-pressure capacitively coupled RF discharge argon plasma - Aadim, Kadhim A.; Hussain, Ali A-K; Yaseen, Waleed I. (Iraqi Journal of Physics, 2019)
Low-pressure capacitively coupled RF discharge Ar plasma has been studied using Langmuir probe. The electron temperature, electron density and Debay length were calculated under different pressures and electrode gap. In this work the RF Langmuir probe is designed using 4MHz filter as compensation circuit and I-V probe characteristic have been investigated. The pressure varied from 0.07 mbar to 0.1 mbar while electrode gap varied from 2-5 cm. The plasma was generated using power supply at 4MHz frequency with power 300 W. The flowmeter is used to control Argon gas flow in the range of 600 standard cubic centimeters per minute (sccm). The electron temperature drops slowly with pressure and it’s gradually decreased when expanding the electrode gap. As the gas pressure increases, the plasma density rises slightly at low gas pressure while it drops little at higher gas pressure. The electron density decreases rapidly with expand distances between electrodes.